2010
DOI: 10.1681/asn.2009070760
|View full text |Cite
|
Sign up to set email alerts
|

PKC-δ Promotes Renal Tubular Cell Apoptosis Associated with Proteinuria

Abstract: Proteinuria may contribute to progressive renal damage by inducing tubulointerstitial inflammation, fibrosis, and tubular cell injury and death, but the mechanisms underlying these pathologic changes remain largely unknown. Here, in a rat kidney proximal tubular cell line (RPTC), albumin induced apoptosis in a time-and dose-dependent manner. Caspase activation accompanied albumin-induced apoptosis, and general caspase inhibitors could suppress this activation. In addition, Bcl-2 transfection inhibited apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 38 publications
0
46
0
Order By: Relevance
“…Lee and Han (24) showed that a higher albumin concentration (3-20 mg/ml) activates Ca 2ϩ -dependent PKC, which phosphorylates the epidermal growth factor receptor in primary rabbit PT cells leading to cell growth. However, Li et al (30) showed that albumin (10 -40 mg/ml) activates PKC␦, promoting tubular cell injury and death during albuminuria in a rat proximal tubular cell line. Here, we observed that a higher albumin concentration (10 -20 mg/ml) did not change PKC activity compared with controls in the absence of albumin.…”
Section: Discussionmentioning
confidence: 99%
“…Lee and Han (24) showed that a higher albumin concentration (3-20 mg/ml) activates Ca 2ϩ -dependent PKC, which phosphorylates the epidermal growth factor receptor in primary rabbit PT cells leading to cell growth. However, Li et al (30) showed that albumin (10 -40 mg/ml) activates PKC␦, promoting tubular cell injury and death during albuminuria in a rat proximal tubular cell line. Here, we observed that a higher albumin concentration (10 -20 mg/ml) did not change PKC activity compared with controls in the absence of albumin.…”
Section: Discussionmentioning
confidence: 99%
“…However, excessive proteinuria brings abundant FFAs into tubular mitochondria, thus accelerating ROS production (105). In proximal tubular cells, albumin activates PKC␦ to induce Bax activation, resulting in mitochondrial outer membrane leakage of apoptogenic factors such as cytochrome, following by apoptosis (81). Furthermore, reabsorption of albumin activates the GTPase Rac1 in proximal tubule cells, resulting in ROS production (147).…”
Section: Acquired Mitochondrial Dysfunction In Kidney Diseasementioning
confidence: 99%
“…Recent evidence has demonstrated that proteinuria also contributes to the progression of kidney diseases (5,8). The direct effects of proteinuria on epithelial cell phenotypic transition (23), cell apoptosis (12), tubulointerstitial inflammation (2), and subsequent fibrotic response (13) may serve as the major factors in the progression of chronic kidney diseases (CKDs). However, the detailed molecular mechanisms of this pathological process remain elusive, hindering the identification of specific and effective therapeutic targets for the treatment of proteinuria-associated kidney injury.…”
mentioning
confidence: 99%